A white paper from the FEBS Education and Training Conference: challenges, opportunities, and action plans for transforming molecular life sciences education - Ly Villo; Nino Sincic; Luciane V. Mello; Manuel Joao Costa; Didier Picard; Francesco Malatesta; Jerka Dumic; Ferhan G. Sagin (FEBS Open Bio)
The inaugural FEBS Education and Training Conference (ETC) was held in Türkiye, in 2024. This first‐ever Molecular Life Sciences Education Conference in Europe was organized by the FEBS Education and Training Committee and it was a groundbreaking event that brought together educators and scientists to explore how to enhance education and training in molecular life sciences. The conference explored a wide range of critical themes, for example—digital revolution, active learning and student engagement, multidisciplinary teaching and learning, transitions and inclusivity in education, students' self‐assessment, and self‐regulated learning. The discussions and presentations underscored the pressing need for transformation in how academics and researchers approach teaching and learning. Such shift is driven by rapid technological advancements, societal shifts, and the evolving demands of the scientific landscape. This document synthesizes key insights, discussions, and recommendations from the conference and proposes actionable strategies for all stakeholders in the field—institutions, educators and students—to address current challenges in education and training in molecular life sciences.